O chiste em Tutaméia: riso que (des)vela - Guadalupe Segunda, Maria (2009)
The aim of this paper is to present the study of the laughter in Tutaméia, by João Guimarães Rosa, throughtout the four forewords and ten novels selected from the author s literary work. It is based on the psychoanalytical theory of Sigmund Freud and Jacques Lacan about the laughter (and delight in the humorous nuances) and the unconscious mind. By taking the laughter as the point of exploitation and understanding, the narration can be understood from an esthetical pattern established on the variety of orallity retained by the narrator and the cordel pamphlets (known as string literature ) and its bypassing on the classical literature and the popular literature revealing its own logical linguistic and conception apart from the official one. It is taken a comparative conception of life in the François Rabelais characters and some characters from Tutaméia having Melim-Meloso as a paradigm showing how one s life can be happy in spite of all adversities by using laughter as the antidote potion against human being s misery and pain to achieve sense of freedom and pleasure